Malachite green : properties and uses - Laursen, Rosa M. (Chemistry research and applications series., 2020)
Malachite green is a green, crystalline, water soluble, triphenyl methylene chloride salt with several sources, including the dye industry, textile industry, medical fields and aquatic life. Its leuco form is electrically neutral and undergoes photoionization that yields the cationic form of malachite green. This reaction provides desirable features that can be used to control the molecular properties via electrostatic interaction/repulsion. The usage of malachite green was banned worldwide by the Food and Drug Administration in 2002, however it is still used in some places due to its low cost and the lack of suitable alternatives. As such, the removal of malachite green by using Kocuria marina DAGII cells in a fixed-bed column is discussed. In recent years, the use of microbial biomass for the decolorization and degradation of textile industry wastewater has become a promising alternative due to its eco-friendliness and low cost, where selected bacteria, algae, yeast and fungi are used to replace existing treatment processes.